2022
DOI: 10.1108/jcefts-08-2021-0046
|View full text |Cite
|
Sign up to set email alerts
|

Board gender diversity and environmental disclosure: evidence from the banking sector

Abstract: Purpose This study aims to examine the relationship between board gender diversity and environmental disclosure (ED) in the banking sector. Design/methodology/approach Data pooled from Bloomberg database on 2,116 banks from the period of 2007 to 2016 ends up with 7,951 observations. Panel regression model that include random effects was used to test study hypothesis. Findings The findings showed that when female board members were between 21% and 50%, it had a significant positive effect on the ED disclosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…Gender diversity within a bank's board of directors has a significant impact on corporate social responsibility. Research Buallay &;Alhalwachi, (2022) shows that the presence of women on councils in equal proportions, particularly when the number of female councillors ranges between 21% and 50%, can increase the disclosure of social responsibility, especially in the environmental context. This is because gender diversity on the board brings broader perspectives and more diverse decision-making.…”
Section: Social Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Gender diversity within a bank's board of directors has a significant impact on corporate social responsibility. Research Buallay &;Alhalwachi, (2022) shows that the presence of women on councils in equal proportions, particularly when the number of female councillors ranges between 21% and 50%, can increase the disclosure of social responsibility, especially in the environmental context. This is because gender diversity on the board brings broader perspectives and more diverse decision-making.…”
Section: Social Responsibilitymentioning
confidence: 99%
“…Several studies have shown that the presence of diverse genders in the board of directors (GD) has an important impact on the disclosure of environmental, social, and governance (ESG) issues. Buallay &;Alhalwachi, (2022) found that gender diversity on the board of directors has a significant positive influence on environmental disclosure (ED) in the banking sector. The results showed that when female board members were between 21% and 50%, it had a significant positive effect on ED disclosure.…”
Section: Esgmentioning
confidence: 99%
“…Flabbi et al (2019) argue that in regions such as Latin America, where board gender diversity is in transition, “male chauvinism” and gender stereotypes, there are fewer female directors on the boards. With fewer female directors on boards, they may be ineffective in influencing ESG disclosure, as the significant positive influence of female directors on ESG disclosure may depend on their mass (Buallay & Alhalwachi, 2022). Although various theories have been utilized to explain the relationship between female directors and ESG‐related disclosures, this study focuses on the stakeholder and agency theories to hypothesize this relationship (Galbreath, 2018; Lee & Isa, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…On the one hand, many researchers have found a significant positive relationship between ESG integration and firm performance (Deng and Cheng, 2019;Aouadi and Marsat, 2018;Zhao et al, 2018;Velte, 2017;Lins et al, 2017). On the other hand, other scholars have identified a negative relationship (Duque-Grisales and Aguilera-Caracuel, 2019;Landi and Sciarelli, 2019;Buallay and Alhalwachi, 2022;Buallay, 2020;Mokadem and Muwafak, 2021;Awwad and El Khoury, 2021) or an insignificant relationship (Atan et al, 2018) between the two. Benlemlih and Bitar (2018) state that sustainability reporting and its effect on firm performance vary with the institutional and regulatory setting.…”
Section: Introductionmentioning
confidence: 99%